2017
DOI: 10.1007/s00779-017-1018-0
|View full text |Cite
|
Sign up to set email alerts
|

Using thermal stimuli to influence affect in different picture display sizes

Abstract: The ability of images to evoke emotions in people has been well documented in previous research, as well as the differences in the emotional perception of images when viewed on different-sized screens and device types. The ability of thermal stimuli to evoke emotions in people when used for media augmentation has also been examined. However, little is known about how thermal stimuli can be used to enhance or reduce affect in images with varying emotional properties displayed in different sizes or on different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The transcripts were analyzed using the Constant Comparative Method (CCM) [48], a data analysis method of Grounded Theory. This is a method of qualitative data analysis that aims to allow the generation of themes using specific coding and analytic procedures which has been used successfully in past HCI/HRI studies [49], [50]. The analysis was verified by an experienced HCI researcher external to the project.…”
Section: Methodsmentioning
confidence: 99%
“…The transcripts were analyzed using the Constant Comparative Method (CCM) [48], a data analysis method of Grounded Theory. This is a method of qualitative data analysis that aims to allow the generation of themes using specific coding and analytic procedures which has been used successfully in past HCI/HRI studies [49], [50]. The analysis was verified by an experienced HCI researcher external to the project.…”
Section: Methodsmentioning
confidence: 99%
“…The temperature changes in positive (warm) and negative (cool) directions influenced the valence and arousal levels of the messages they heard. Warming temperature has been shown to elicit greater emotional arousal than cooling temperatures, while individuals viewed images that elicit specific emotions [15], [16]. It was also demonstrated that a 3°C temperature change increased arousal levels compared to no temperature change.…”
Section: B Effect Of Temperature Changes On Emotional Experiencementioning
confidence: 96%
“…Modifications to thermal experience can either alter the ambient environment (Scott et al, 2011) or deliver a thermal stimulus to specific body regions (Akazue et al, 2016; Wilson et al, 2011). Here, we focus on technologies that are or could be made wearable, specifically for body heating in cool environments.…”
Section: Introductionmentioning
confidence: 99%